Respuesta :
Answer:
x = 6
Step-by-step explanation:
Using the rules of logarithms
• log x - log y ⇔ log ([tex]\frac{x}{y}[/tex] )
• [tex]log_{b}[/tex] x = n ⇔ x = [tex]b^{n}[/tex]
Given
log(5x) - log(x - 3) = 1
log ( [tex]\frac{5x}{x-3}[/tex] ) = 1, then
[tex]\frac{5x}{x-3}[/tex] = [tex]10^{1}[/tex] = 10 ( cross- multiply )
10(x - 3) = 5x
10x - 30 = 5x ( subtract 5x from both sides )
5x - 30 = 0 ( add 30 to both sides )
5x = 30 ( divide both sides by 5 )
x = 6
Answer:
x =6
Step-by-step explanation:
log(5x) - log(x - 3) = 1
Recall that the logarithm of a fraction is the difference of the logarithms,
so, the difference between two logarithms is logarithm of the fraction. Then,
[tex]\begin{array}{rcll}\\\\\log \dfrac{5x}{x-3} & = & 1 &\\\\\dfrac{5x}{x - 3} & = & 10 & \text{Took the antilogarithm of each side}\\\\5x & = & 10(x - 3) & \text{Multiplied each side by x - 3}\\5x & = & 10x - 30 & \text{Distributed the 10}\\-5x & = & -30 & \text{Subtracted 10 x from each side}\\x & = & \mathbf{6} & \text{Divided each side by -5}\\\end{array}[/tex]
Check:
[tex]\begin{array}{rcl}\log(5\times6) - \log (6 - 3) & = & 1\\\log 30 - \log 3 & = &1\\\\\log \dfrac{30}{3} & = & 1\\\\\log 10 & = & 1\\1 & = & 1\\\end{array}[/tex]
OK.